2018
DOI: 10.1111/ajr.12435
|View full text |Cite
|
Sign up to set email alerts
|

What do mental health workers in the bush think about mental health nurse prescribing? A cross‐sectional study

Abstract: The attitudes of rural South Australian mental health workers are not a barrier to mental health nurse prescribing. The implementation and sustainability of mental health nurse prescribing will require additional staff training in psychopharmacology and a governance framework to assure quality and safety. Policy-makers need to focus their attention on the uptake of mental health nurse prescribing in parts of Australia that struggle to attract and retain psychiatrists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…Health care professionals perceive that patients would benefit from the proposed nurse prescribing in mental health in Australia (Muyambi et al, 2018). To advance future implementation of nurse prescribing under supervision, further research is warranted to ascertain not only the perceived merits of this model but also to evaluate the safety and impact of this model on patient care and population health outcomes in the longer term.…”
Section: Resultsmentioning
confidence: 99%
“…Health care professionals perceive that patients would benefit from the proposed nurse prescribing in mental health in Australia (Muyambi et al, 2018). To advance future implementation of nurse prescribing under supervision, further research is warranted to ascertain not only the perceived merits of this model but also to evaluate the safety and impact of this model on patient care and population health outcomes in the longer term.…”
Section: Resultsmentioning
confidence: 99%
“…The view by the metropolitan focus group does not reflect the attitudes of MHWs in country South Australia towards MHN prescribing. In an attitudinal survey of 93 MHWs employed by the Country Health South Australia Local Health Network for Mental Health, authors found that the respondents showed positive attitudes towards MHN prescribing although they expressed concerns about safety, educational preparation and supervision structures (Muyambi et al, ). Perhaps the shortage of psychiatrists in regional areas influenced the opinions of the regional group; similarly, the metropolitan group's opinions may have been affected by them practising in a healthcare environment that has adequate access to psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…The regional focus group was more positive about granting prescribing rights for MHNs, while the metropolitan focus group adopted a more cautious view. (Muyambi et al, 2018). Perhaps the shortage of psychiatrists in regional areas influenced the opinions of the regional group; similarly, the metropolitan group's opinions may have been affected by them practising in a healthcare environment that has adequate access to psychiatrists.…”
Section: One State Two Worldsmentioning
confidence: 99%
“…We revisited this topic in the context that the distribution of GPs is unbalanced across areas and does not correspond with need in Australia in recent years [12][13][14][15][16]. There is higher availability of GPs in urban and inner regional areas [17], although there is also variation within urban areas (as shown in our data).…”
Section: Introductionmentioning
confidence: 96%